Studying the effect of changing Input conditions on MMF using MGDM technique - Zahraa H. Mohammed; Radhi Sehen Issa; Sadiq Ahmed (Institute of Advanced Engineering and Science, 2022)
The mode group diversity multiplexing (MGDM) multicast technology uses optical multiple input and output (O-MIMO) technology to provide greater capacity and the ability to transmit information over multi-mode fiber (MMF). The MGDM system has a benefit in terms of capacity expansion, which led to interest in its use in most optical communications. The MGDM exploits the optical fiber bandwidth by inserting spatial light detection, which increases the capacity of the MMF. This research aims to study the optical systems used for the MGDM technology, and to identify the methods of their analysis and design of O-MIMO systems to increase the amplitude of this signal. The conditions of light entry into the optical fiber such as typical spot size, radial displacements, angle, wavelength, and radius of the detectors sections are improved. Numerical MATLAB simulation is used to improve the amplitude of graded index multimode fiber (GI-MMF) and compared to the existing aggregation systems. Moreover, this method was simulated to improve the input and detection conditions to increase the O-MIMO capacity using the MGDM technique. Finally, the capacity of the MGDM system was studied and compared with different channels, and it is noticed that the capacity of the system increases with increasing the number of channels.